2015
DOI: 10.1097/ftd.0000000000000151
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Immunochemical Methods, PETINIA and EMIT, With That of HPLC-UV for the Routine Monitoring of Mycophenolic Acid in Heart Transplant Patients

Abstract: The new immunochemical PETINIA method was associated with significantly higher MPA concentrations in routine therapeutic drug monitoring samples from heart transplant patients. The magnitude of the MPA overestimation was similar to that observed by use of the EMIT method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…Further in-depth statistical analysis using BlandAltman analysis or Passing Bablok regression confirmed that the use of either of the two enzymatic assays would lead to a positive bias in the estimation of MPA in the routine or pharmacokinetic samples in the patients. While the bias was 33.48% for PETINA assay, it ranged from 24.5 to 42.77% in the case of EMIT assay as compared with the reference HPLC method (Kunicki et al, 2015). A few takeaways from this report included the following: (a) the bias in the results (enzymatic vs HPLC) was directly proportional to MPA concentration; (b) one of the culprits for over estimation of MPA levels by enzymatic assays was the AcMPAG metabolite; and (c) cross-reactivity with other MPA metabolites may have a role to play in the observed positive bias (Kunicki et al, 2015).…”
Section: Measurement Of Mpa In Vitreous Humormentioning
confidence: 87%
See 2 more Smart Citations
“…Further in-depth statistical analysis using BlandAltman analysis or Passing Bablok regression confirmed that the use of either of the two enzymatic assays would lead to a positive bias in the estimation of MPA in the routine or pharmacokinetic samples in the patients. While the bias was 33.48% for PETINA assay, it ranged from 24.5 to 42.77% in the case of EMIT assay as compared with the reference HPLC method (Kunicki et al, 2015). A few takeaways from this report included the following: (a) the bias in the results (enzymatic vs HPLC) was directly proportional to MPA concentration; (b) one of the culprits for over estimation of MPA levels by enzymatic assays was the AcMPAG metabolite; and (c) cross-reactivity with other MPA metabolites may have a role to play in the observed positive bias (Kunicki et al, 2015).…”
Section: Measurement Of Mpa In Vitreous Humormentioning
confidence: 87%
“…While the bias was 33.48% for PETINA assay, it ranged from 24.5 to 42.77% in the case of EMIT assay as compared with the reference HPLC method (Kunicki et al, 2015). A few takeaways from this report included the following: (a) the bias in the results (enzymatic vs HPLC) was directly proportional to MPA concentration; (b) one of the culprits for over estimation of MPA levels by enzymatic assays was the AcMPAG metabolite; and (c) cross-reactivity with other MPA metabolites may have a role to play in the observed positive bias (Kunicki et al, 2015). While it may be difficult to exactly pin-point the overestimation of MPA rendered by enzymatic assays, the published data collectively suggest that the bias could be >20% in many instances.…”
Section: Measurement Of Mpa In Vitreous Humormentioning
confidence: 87%
See 1 more Smart Citation
“…The quantification of MPA can be performed by immunoassays commercially available (Dasgupta, Tso, & Chow, ; Kunicki, Pawinski, Boczek, Was, & Bodnar‐Broniarczyk, ); however, these methods can overestimate MPA plasma concentration as a result of cross‐reactivity of MPA metabolites with the monoclonal antibodies, resulting in limited specificity and sensitivity (Buchwald et al, ; Guo et al, ). One option to improve MPA quantification is applying ultra‐performance liquid chromatography–tandem mass spectrometry (UPLC–MS/MS) methods.…”
Section: Introductionmentioning
confidence: 99%
“…Certain immunoassays, such as enzyme‐multiplied immunoassay technique (EMIT), cloned enzyme donor immunoassay (CEDIA), Roche enzymatic assay or recently developed particle enhanced turbidimetric inhibition immunoassay (PETINIA), produce biased results due to cross‐reactivity with the minor but pharmacologically active MPA metabolite – acyl glucuronide (AcMPAG). In consequence, MPA concentrations measured by immunoassays can be overestimated (Dasgupta, ; Dasgupta, Tso, & Chow, ; Kelly & Butch, ; Kunicki, Pawiński, Boczek, Waś, & Bodnar‐Broniarczyk, ). Therefore, high‐performance liquid chromatography (HPLC) combined with either ultraviolet (UV) or mass spectrometric (MS) detector is considered as a standard method for MPA determination (Dasgupta, , b).…”
Section: Introductionmentioning
confidence: 99%